만성 림프구성 백혈병에 대한 최신 지견 - 조희정; Hee Jeong Cho; 손상균; Sang Kyun Sohn (The Korean journal of medicine, 2021)
Chronic lymphocytic leukemia (CLL), characterized by monoclonal B-cell accumulation and highly variable clinical manifestations that range from an indolent to an aggressive course, is rare in Korea. Asymptomatic patients with early stage CLL can be followed up without treatment; however, those with active or advanced disease require treatment immediately after diagnosis, for symptom alleviation and prolonging survival. Previously, chemotherapy using cytotoxic agents was the only therapeutic option available for patients with CLL. Research has provided a deeper understanding of the pathophysiology of the disease, and novel agents such as monoclonal antibodies and small-molecule inhibitors that target specific sites on leukemic cells have been introduced. The advent of these new drugs has led to improved clinical outcomes in patients with CLL. Currently, Bruton’s tyrosine kinase inhibitors or B-cell lymphoma-2 inhibitors are recommended as frontline therapy, prior to the administration of cytotoxic agents or combination therapy with monoclonal antibodies. In this article, we review the diagnosis and prognosis of CLL, in addition to the clinical implications of the various therapeutic options. (Korean J Med 2021;96:195-208)